Phaseolus lunatus L.: pulse seeds phenotype image analysis - de Jesus Dantas, Saulo [UNESP]; Torres, Maria Fernanda Oliveira; Silva-Mann, Renata [UNESP]; Vargas, Pablo Forlan [UNESP] (Springer Nature, 2023)
The locally cultivated creole varieties of Phaseolus lunatus are adapted to specific climatic and environmental conditions. Family farmers and local communities preserve and multiply their seeds over generations, promoting genetic diversity, food and nutritional security, and agricultural sustainability. This species has great geno-phenotypic diversity, which can be harnessed in breeding programs if accurately characterized. We evaluated the phenotypic variations of P. lunatus seeds from 13 varieties in three states (Sergipe, Bahia, and Alagoas) using image analysis. We estimated the weight of 100 seeds using a precision analytical balance and obtained morphometric measurements, including area, maximum diameter, and minimum diameter, using Groundeye (TBit®) imaging equipment and software. We also recorded dominant color and RGB color system descriptors. The morphometric variables underwent variance analysis using the F-test, and the means were clustered using the Scott-Knott test at 5% significance level. The data underwent Pearson Correlation Analysis (t-Student at 5%), were grouped based on dissimilarity using the UPGMA method, and were represented in a dendrogram. We also performed Principal Component Analysis on the evaluated characteristics. The dominant color of the seeds was predominantly orange in nine varieties. Morphometry showed a positive and significant association. The dendrogram revealed two homogeneous and distinct groups, and the first two principal components accounted for 86.80% of the genotypic variation. Therefore, high-resolution images for phenotypic characterization of creole lima bean seeds are a promising non-destructive tool for selection purposes.
Keywords: Genetic breeding; Genetic diversity; Germplasm; Lima bean; Seed biometry